Complete genetic analysis of plasmids carrying mcr-1 and other resistance genes in an Escherichia coli isolate of animal origin. (19th December 2016) - Li, Ruichao; Xie, Miaomiao; Lv, Jingzhang; Wai-Chi Chan, Edward; Chen, Sheng
Abstract : Objectives: To investigate the genetic features of three plasmids recovered from an MCR-1 and ESBL-producing Escherichia coli strain, HYEC7, and characterize the transmission mechanism of mcr-1 . Methods: The genetic profiles of three plasmids were determined by PCR, S1-PFGE, Southern hybridization and WGS analysis. The ability of the mcr-1 -bearing plasmid to undergo conjugation was also assessed. The mcr-1 -bearing transposon Tn 6330 was characterized by PCR and DNA sequencing. Results: Complete sequences of three plasmids were obtained. A non-conjugative phage P7-like plasmid, pHYEC7- mcr1, was found to harbour the mcr-1 -bearing transposon Tn 6330, which could be excised from the plasmid by generating a circular intermediate harbouring mcr-1 and the IS Apl1 element. The insertion of the circular intermediate into another plasmid, pHYEC7-IncHI2, could form pHNSHP45-2, the original IncHI2-type mcr-1 -carrying plasmid that was reported. The third plasmid, pHYEC7-110, harboured two replicons, IncX1 and IncFIB, and comprised multiple antimicrobial resistance mobile elements, some of which were shared by pHYEC7-IncHI2. Conclusions: The Tn 6330 element located in the phage-like plasmid pHYEC7- mcr1 could be excised from the plasmid and formed a circular intermediate that could be integrated into plasmids containing the IS Apl1 element. This phenomenon indicated that Tn 6330 is a key element responsible for widespread dissemination of mcr-1 among various types of plasmids and bacterial chromosomes. The dissemination rate of such an element may be further enhanced upon translocation into phage-like vectors, which may also be transmitted via transduction events.